2009
DOI: 10.1243/09544062jmes1467
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of interactions between a flame bubble with an incident shock wave and its focusing wave

Abstract: The numerical investigations of interactions between a flame bubble with an incident shock wave (IW) and its focusing wave (FW) in a reactive CH 4 -O 2 -N 2 mixture are presented. The time-dependent, two-dimensional axisymmetric, reactive Navier-Stokes equations, with detailed chemical mechanisms, are employed to simulate the multiple shock-flame interactions process. The effects of the IW Mach number and chemical reactivity of mixture on flame structure and evolution are examined. The results of simulations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some studies have neglected the effect of bridge flexibility, and some have considered it in their calculations in different ways. Many studies have been done on the bridge superstructure with rigid support under wave loads [6,15,17,[22][23][24]. e bridge deck with flexible support is a problem that has not been adequately studied yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have neglected the effect of bridge flexibility, and some have considered it in their calculations in different ways. Many studies have been done on the bridge superstructure with rigid support under wave loads [6,15,17,[22][23][24]. e bridge deck with flexible support is a problem that has not been adequately studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…e bridge deck with flexible support is a problem that has not been adequately studied yet. Today, powerful software packages are made by computers that can analyze fluid-solid interaction (FSI) problems accurately, but using them to analyze any problem requires verification with similar laboratory models [23]. As an experimental work that considered deck flexibility, we can mention Bradner et al ey made one span of the I-10 Bridge over Escambia Bay with a 1: 5 scale in the Oregon State University wave flume.…”
Section: Introductionmentioning
confidence: 99%
“…The problems of compressible two-phase flow present in many research fields, such as aero-and astronautics, mechanics, material science, astrophysics, nuclear engineering even medical sciences. Several typical examples are underwater explosion, biomedical ultrasound and shock wave lithotripsy [1,2] and shock-induced mixing of liquid fuel droplets in scramjet combustor [3], etc. The related researches are valuable from both theoretical and application points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Linear and weakly nonlinear interaction analyses of shock-interface interaction problems have been studied in detail, starting with the original work of Richtmyer, 6 continuing with the nonlinear models of Zhang and Sohn, 7 up to detailed numerical simulations of reactive 8 and non-reactive 9 systems; reviews on RMI are found in Refs. 10 and 11.…”
Section: Introductionmentioning
confidence: 99%